Formation of the quality of wheat grain by extremely low frequency electromagnetic field treatment - Stankevych, Georgii; Kovra, Yurii; Borta, Alla (Technology audit and production reserves (Online), 2022)
The object of the study is the treatment of wheat grain with an electromagnetic field (EMF) of extremely low frequencies (ELF), the subjects of the study are the quality indicators of wheat seed grain of the Shestopalivka variety 2019 and 2020 crops grown in the Odesa region. (Ukraine). Problematic issues in the treatment of wheat grain with ELF EMF are the rationale for the duration of treatment of grain and the frequencies of EMF that improves the quality of seeds. The studies used methods of laboratory determination of seed quality indicators, calculation of statistical characteristics of the length of sprouts, and graphical methods for interpreting the results of studies. The studies substantiated the modes of treatment wheat grain with ELF EMF, which improves the quality of seeds and reduces the energy intensity of treatment. The effect of the duration of grain treatment and the frequency of EMF on the germination and characteristics of the length of seed shoots was studied. It has been established that, compared with untreated grain, the treatment of grain with an EMF with a frequency of 30 Hz, a magnetic induction of 10 mT for 6 minutes increases grain germination by 2–3 %, gives longer and 1.44–1.53 times more uniformly sprouted sprouts. Treatment within 60 min. reduces up to 9 % the germination of grain, the size of the shoots, increases their unevenness in length. The effect of seed germination activation by EMF treatment increases after 19 days of storage. Treatment of wheat grain in 2019 with ELF EMF at a frequency of 15–17 Hz with a magnetic induction of 10 mT for 6 min. changes germination within ±3 % control. The germination of the treated grain of wheat in 2020 of the crop decreases relative to the control to 13 % (with the exception of the frequency of 16.5 Hz, at which it did not change). Thus, the treatment of wheat grain with EMF makes it possible to influence the quality of seed grain. The results obtained encourage further research with a wider range of regime parameters and areas of wheat cultivation. Об'єктом дослідження є обробка зерна пшениці електромагнітним полем (ЕМП) вкрай низьких частот (ВНЧ), предмети дослідження – показники якості насіннєвого зерна пшениці сорту Шестопалівка 2019 та 2020 років врожаїв, вирощених в Одеській обл. (Україна). Проблемними питаннями при обробці зерна пшениці ЕМП ВНЧ є обґрунтування тривалості обробки зерна та частот ЕМП, що поліпшують насіннєву якість. У дослідженнях використовували методи лабораторного визначення показників якості насіння, розрахунку статистичних характеристик довжини паростків та графічні методи інтерпретації результатів досліджень. У дослідженнях обґрунтовані режими обробки зерна пшениці ЕМП ВНЧ, що підвищують якість насіння та знижують енергоємність обробки. Досліджено вплив тривалості обробки зерна та частоти ЕМП на схожість і характеристики довжини паростків насіння. Встановлено, що порівняно з необробленим зерном, обробка зерна ЕМП з частотою 30 Гц, магнітною індукцією 10 мТл впродовж 6 хв. підвищує на 2–3 % схожість зерна, дає довші та у 1,44–1,53 рази більш рівномірно пророслі паростки. Обробка протягом 60 хв. знижує до 9 % схожість зерна, розміри паростків, збільшує їх нерівномірність за довжиною. Ефект активації схожості насіння обробкою ЕМП збільшується після 19 діб зберігання. Обробка зерна пшениці 2019 р. врожаю ЕМП ВНЧ за частот 15–17 Гц з магнітною індукцією 10 мТл протягом 6 хв. змінює схожість у межах ±3 % від контролю. Схожість обробленого зерна пшениці 2020 р. врожаю знижується відносно контролю до 13 % (за виключенням частоти 16,5 Гц, за якої вона не змінилась). Таким чином, обробка зерна пшениці ЕМП дозволяє впливати на якість насіннєвого зерна. Отримані результати спонукають до продовження досліджень з більш широким діапазоном режимних параметрів та ареалів вирощування пшениці.